Expectations of Deep Learning Curriculum-Based Learning Review of Government Regulation Number 4 Of 2022 Concerning National Education Standards - Zarkasyi, Ahmad (Progressive Journal of Educational Science, 2025)
This article describes the principles and outcomes of the "deep learning" curriculum: an integrative analysis of the Government Regulation Number 4 Of 2022 Concerning National Education Standards. This study uses a qualitative approach with library research, which collects data and information from various library materials, such as curriculum theory, journals, and education standards laws in Indonesia. Based on the research results, it can be concluded that the basic principles of the outcome-based curriculum in the Minister of Education, Culture, Research, and Technology Regulation Number 12 of 2024 are based on the following principles: focus on clear and measurable learning outcomes, student-centered approach, performance-based assessment, continuous improvement. The three dimensions of the deep learning-based curriculum are mindfulness, calmness, and concentration. Meaningful learning means learning full of experience. Joyful learning means learning that is enjoyable.